Hypotonic lysis of mammalian erythrocytes in chlorpromazine presence - Сєміонова, К.А.; Єршова, Н.А.; Орлова, Н.В.; Шпакова, Н.М. (Eastern European Scientific Journal. 2016. № 2. P. 7-17, 2016)
When studying hypotonic sensitivity of bovine, equine, canine and human erythrocytes the human and canine erythrocytes have been shown to be more sensitive to the effect of hypotonic media. Chlorpromazine manifests a high antihemolytic activity under conditions of hypotonic lysis of mammalian erythrocytes. Maximal efficiency of chlorpromazine has been demonstrated for the bovine cells and minimal one was done for canine erythrocytes.
Semionova EA, Iershova NA, Orlova NV, Shpakova NM. Hypotonic lysis of mammalian erythrocytes in chlorpromazine presence. Eastern European Scientific Journal. 2016; 2: 7-17
Keywords: гипотонический стресс; эритроциты; амфифильные соединения